Identification and characterization of a set of monocot BAHD monolignol transferases. Issue 1 (3rd February 2022) - Smith, Rebecca A; Beebe, Emily T; Bingman, Craig A; Vander Meulen, Kirk; Eugene, Alexis; Steiner, Alexander J; Karlen, Steven D; Ralph, John; Fox, Brian G
Abstract: Plant BAHD acyltransferases perform a wide range of enzymatic tasks in primary and secondary metabolism. Acyl-CoA monolignol transferases, which couple a CoA substrate to a monolignol creating an ester linkage, represent a more recent class of such acyltransferases. The resulting conjugates may be used for plant defense but are also deployed as important "monomers" for lignification, in which they are incorporated into the growing lignin polymer chain. p -Coumaroyl-CoA monolignol transferases (PMTs) increase the production of monolignol p -coumarates, and feruloyl-CoA monolignol transferases (FMTs) catalyze the production of monolignol ferulate conjugates. We identified putative FMT and PMT enzymes in sorghum ( Sorghum bicolor ) and switchgrass ( Panicum virgatum ) and have compared their activities to those of known monolignol transferases. The putative FMT enzymes produced both monolignol ferulate and monolignol p -coumarate conjugates, whereas the putative PMT enzymes produced monolignol p -coumarate conjugates. Enzyme activity measurements revealed that the putative FMT enzymes are not as efficient as the rice ( Oryza sativa ) control OsFMT enzyme under the conditions tested, but the SbPMT enzyme is as active as the control OsPMT enzyme. These putative FMTs and PMTs were transformed into Arabidopsis ( Arabidopsis thaliana ) to test their activities and abilities to biosynthesize monolignol conjugates for lignification in planta. The presence of ferulates and p -coumarates on the lignin of these transformants indicated that the putative FMTs and PMTs act as functional feruloyl-CoA and p -coumaroyl-CoA monolignol transferases within plants. Abstract : A group of identified BAHD acyltransferases function as feruloyl-CoA monolignol transferases and/or p -coumaroyl-CoA monolignol transferases in vitro and in planta.